PENGARUH EFEKTIVITAS IKLAN EXCLUSIVE SERIES DEWISANDRA TERHADAP BRAND IMAGE DAN KEPUTUSAN PEMBELIANKOSMETIK WARDAH DI KOTA PEKANBARU - Masikah, Afifah; Alwie, Alvi Furwanti (Jurnal Tepak Manajemen Bisnis, 2016)
This study aimed to analyze the influence The Influence OfAdvertisement Exclusive Series Dewi Sandra Wardah Cosmetics TowardBrand Image and Purchase Decision In Pekanbaru.this study consist of fivevariables the quality of the message (X1),advertising appeal (X2),advertisement frequency (X3), Brand Image (Y1) and Purchase Decision (Y2)Methods of Sampling used purposive sampling, with criteria, the sample is livein Pekanbaru, woman age above 17 years. Wardah cosmetic users anddecision makers (decider), with a total of 154 respondents. This studyconducted at the outlet cosmetic Wardah SKA mall, Ciputra Seraya mall,Pekanbaru mall. Data collection was performed by giving questionnaires tothe respondents and data analysis used is Path analysis with SPSS (StatisticalPackage for Social Science) version 22.Research results show that high thequality of the message, advertising appeal, advertisement frequency, brandimage increasing purchase decision Wardah cosmetics but had negativeinfluence towards advertisement frequency Exclusive Series Dewi Sandra.Brand Image positively mediated influence message quality and advertisingappeal towards purchase decision Wardah Cosmetics, but had negativeinfluence towards advertisement frequency. for the company, its highlyrecommended to increasing the advertisement frequency Exclusive SeriesDewi Sandra and maintain the time on noon and night, at times the consumeris at restKeywords: The quality of the message, advertising appeal, advertisementfrequency, Brand Image and Purchase Decision